Different Traditional Herbal Medicines for the Treatment of Gastroesophageal Reflux Disease in Adults - Dai, Yun-kai; Wu, Yun-bo; Wen, Hao; Li, Ru-liu; Chen, Wei-jing; Tang, Chunzhi; Lu, Liming; Hu, Ling (Frontiers in Pharmacology, 2020)
Background/Aims: Traditional Herbal Medicines (THM) have been being used for gastroesophageal reflux disease (GERD) for a long time, but their clinical evidences are still poor. We evaluated different THM prescriptions for GERD in adults. Methods: Nine online databases from their inception to November 30, 2019 were systematically searched. All relevant randomized controlled trials (RCTs) were included and combined with a Bayesian network analysis. The Cochrane Collaboration’s risk of bias tool and the GRADE profiler version 3.6 were respectively employed to evaluate the evidence quality of outcomes. Results: Seventeen publications involving in 1441 participants were retrieved. Results of our analysis suggested that Jianpi therapy+proton pump inhibitors (PPIs) and Ligan Hewei therapy respectively ranked first in overall clinical efficacy and efficacy under gastroscope; Ligan Hewei therapy+PPIs was the optimum intervention in the improvement of acid regurgitation and heartburn. Conclusion: This research indicates Ligan Hewei therapy and Jianpi therapy, or combined with PPIs, should be recommended as the appropriate complementary and alternative treatments based on the specific characteristics of GERD. However, additional well-designed RCTs with high methodological quality are still needed for future research.